Retraction Notice to â€œThe Role of Positive Emotion as a Mediator between Psychological Capital and Work Engagementâ€ [Journal of Educational, Health and Community Psychology, 2019, 8(2), 85-104] - Nerinda Rizky Firdaus (Universitas Ahmad Dahlan, 2020)
AbstractFollowing a rigorous, carefully concerns and considered review of the article publishedin theJournal of Educational, Health and Community Psychology to article entitled â€œThe Role of Positive Emotion as a Mediator between Psychological Capital and Work Engagementâ€ [Journal of Educational, Health and Community Psychology 2019 8 (2) 85 - 104] DOI http://dx.doi.org/10.12928/jehcp.v8i2.12563. This paper has been found to be in violation of the Journal of Educational, Health and Community Psychology Publication principles and has been retracted. This article has been retracted at the request of the Supervisor of the author, Nerinda Rizky Firdaus (Airlangga University Indonesia), because the author didn't communicate with him to publish the research work in this journal and didn't write his name on the article as responsible to teamwork effort. This practice is count as the unethical publication of the Journal of Educational, Health and Community Psychology.